MODERN ACCOUNTING MANAGEMENT: IMPLEMENTATION OF TECHNOLOGY TO ENHANCE EFFICIENCY IN 100 SMES IN KARANGANYAR REGENCY - Ramadhian Agus Triono Sudalyo; Nurita Elfani Prasetyaningrum (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to analyze the application of technology in modern accounting management and its impact on efficiency in 100 Micro, Small, and Medium Enterprises (MSMEs) in Karanganyar Regency. In an increasingly advanced digital era, the use of technology in accounting management has become an essential need for MSMEs to improve operational and financial efficiency. This efficiency is crucial for MSMEs as it can enhance competitiveness, improve financial management, and aid in more accurate decision-making. The research method employed is semi-structured interviews with MSME owners in Karanganyar Regency. The interviews will cover questions related to the use of technology in accounting management, such as the use of accounting software, digital payment systems, as well as the understanding and skills of human resources related to the use of such technology. The interviews will also delve into the challenges faced by MSMEs in implementing accounting management technology. The data obtained will be analyzed using thematic analysis methods to identify patterns and main themes. The research results are expected to identify concrete benefits gained by MSMEs through the application of technology in accounting management, such as operational efficiency, reduction of human error, better accessibility of financial information, and improved decision-making capabilities. This research can provide valuable insights for MSMEs in Karanganyar Regency and other regions in understanding the importance of applying technology in accounting management. The practical implication of this research is to provide recommendations to MSMEs on steps that can be taken to adopt technology in accounting management, in order to improve business efficiency and competitiveness. These findings can also be applied by MSMEs outside Karanganyar by considering local contexts and specific needs of each region.